HUBUNGAN PERHATIAN ORANG TUA TERHADAP PENINGKATAN MORAL ANAK - Ulfa Hidayatus; Mayrina Eka Prasetyo Budi (Institut Agama Islam Negeri Ponorogo, 2021)
AbstractThis study aims to determine the level of parental attention to children aged 7-12 years in Durenan Village, Sidorejo Magetan District, for Knowing the level of moral development in children aged 7-12 years in Durenan Village, Sidorejo Magetan District, and to find out the relationship between parents' attention to improving the morale of children aged 7-12 years in Durenan Village, Sidorejo Magetan District. This study uses a quantitative approach with correlational research. The data collection technique uses questionnaire and observation techniques. The research data were analyzed using product moment correlation. The results showed the level of parental attention in the category moderate with a percentage of 87.5%, the level of moral development of children is in the medium category with a percentage of 78.13%, and there is a significant relationship between parental attention and moral improvement of children aged 7-12 years in Durenan Village, Sidorejo Magetan District. It is known from the results of calculations using the SPSs, namely the count of 0.929 and r table of 0.349, so that Ha accepted Ho is rejected, which means that there is a significant relationship between parental attention and moral improvement of children aged 7-12 years in Durenan Village, Sidorejo Magetan District.Keywords: parents' attention, children's moral improvement